The Impact of Basic Life Support Education on Knowledge Among Youth Red Cross Members at SMAN 12 Bekasi City, 2024 - Medi Ety, Intan; Pelawi, Arabta M Peraten; Meliyana, Ernauli (Althar Cendikia Education, 2025)
One of the leading causes of death in Indonesia—such as cardiac arrest—requires rapid intervention through Basic Life Support (BLS). Cardiac arrest can occur at any time and may be fatal if not addressed immediately. BLS is a fundamental skill that everyone should possess, as it plays a critical role in increasing the chances of survival in life-threatening situations. Many cardiac arrest cases happen outside of medical settings, known as Out-of-Hospital Cardiac Arrest (OHCA). This study aimed to assess the effect of BLS education on the knowledge of Youth Red Cross (PMR) members at SMAN 12 Bekasi City, considering the observed lack of BLS knowledge among members. A quantitative method with a pre-experimental design was applied, using a one-group pre-test post-test approach. The study involved all 59 PMR members through total sampling. Data analysis using a paired sample t-test showed a significant difference between pre-test and post-test scores, with a p-value of 0.000 < 0.05, indicating that the null hypothesis was rejected. The findings confirm that BLS education had a significant positive effect on the participants’ knowledge levels. The study concluded that there was a notable increase in BLS knowledge among PMR members after the educational intervention.